ORIGIN OF OLIVINE-RICH TROCTOLITES FROM THE OCEANIC LITHOSPHERE: A COMPARISON BETWEEN THE ALPINE JURASSIC OPHIOLITES AND MODERN SLOW SPREADING RIDGES - Sanfilippo, Alessio; Tribuzio, Riccardo (Ofioliti, 2013)
Olivine-rich troctolite bodies occur within lower crust and mantle sections of the Jurassic oceanic lithosphere exposed along the Alpine-Apennine belt. These rocks bear structural and compositional resemblances to the olivine-rich troctolites from slow spreading ridges. The olivine-rich troctolites from the Alpine-Apennine belt contain olivines (Fo = 89-87 mol%) with rounded to embayed morphology and clinopyroxene oikocrysts with high Mg# (90-88). The clinopyroxene oikocrysts have higher Cr2O3  (1.6-1.3 wt%) and lower Ti/Yb than clinopyroxenes in equilibrium typical MORB-type melts. These chemical characteristics were most likely acquired by reaction between an olivine-rich matrix and migrating melts crystallizing clinopyroxene and plagioclase. The pla- gioclases from the olivine-rich troctolites of the Alpine-Apennine belt are commonly poorer in anorthite component (71-61 mol%) than the plagioclases from slow spreading ridge olivine-rich troctolites. The migrating melts involved in the formation of the olivine-rich troctolites from the Alpine-Apennine belt were most likely slightly enriched in Na2O with respect to the basalts normally produced at slow spreading ridges. We attribute this Na2O enrichment to a low de- gree of melting of asthenospheric sources. The olivine-rich troctolites from fossil and modern oceanic lithosphere probably formed at the mantle-crust transi- tion. The occurrence of olivine-rich troctolite bodies within gabbroic sequences is reconciled with a process of dissection and entrapment of the mantle-crust transition during the growth of the lower crust.